2005
DOI: 10.1086/498311
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Levels in Older Men Who Have or Who Are at Risk of Acquiring HIV Infection

Abstract: Most older men at risk for HIV infection have low androgen levels. Injection drug use, high body mass index, HCV infection, and use of psychotropic medications are associated with low androgen levels, and low androgen levels are associated with symptoms of hypogonadism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 37 publications
7
72
1
1
Order By: Relevance
“…The small yet significant difference in sexual activity between HIV-positive and HIV-negative men may be due in part to the significantly greater prevalence of erectile dysfunction among the HIV-positive men. Studies have indicated that HIV infection may be related to decreased androgen levels and erectile dysfunction (Cove & Petrak, 2004;Jung & Schill, 2004;Klein et al, 2005). In fact, a significantly greater percentage of the HIV-positive men in our sample reported taking sildenafil in the past 6 months and ever talking testosterone or other male hormones during their lifetime.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The small yet significant difference in sexual activity between HIV-positive and HIV-negative men may be due in part to the significantly greater prevalence of erectile dysfunction among the HIV-positive men. Studies have indicated that HIV infection may be related to decreased androgen levels and erectile dysfunction (Cove & Petrak, 2004;Jung & Schill, 2004;Klein et al, 2005). In fact, a significantly greater percentage of the HIV-positive men in our sample reported taking sildenafil in the past 6 months and ever talking testosterone or other male hormones during their lifetime.…”
Section: Discussionmentioning
confidence: 57%
“…The Cohort of HIV At-Risk Aging Men's Prospective Study (CHAMPS) is an ongoing longitudinal study of selected outcomes in older men with or at risk for HIV infection (Klein, Lo, Santoro, & Dobs, 2005). Participants were recruited through word of mouth, flyers in HIV and medical clinics, advertisements in the community, and research staff presentations at HIV community groups.…”
Section: Methodsmentioning
confidence: 99%
“…SHBG and 17-OHP were assayed using commercially available reagents from Diagnostic Products Corporation (DPC) (Los Angeles, CA: SHBG sensitivity 0.5nmol/L, intra-assay CV 4.3% and inter-assay CV 8.6%). (19,20) Androstenedione was measured in duplicate using the Coat-aCount assay from DPC (sensitivity 0.140 nmol/L, intra-assay CV 5.7 % and inter-assay CV 8.4%). Serum glucose was analyzed by the Olympus AU400 Chemistry Autoanalyzer using the Olympus Glucose Kit.…”
Section: Methodsmentioning
confidence: 99%
“…Participant recruitment and study design for both studies have been described previously. 35,36 In brief, Ms-enrolled women aged 35- Recruitment for both cohorts was from methadone maintenance clinics, primary care clinics, community newsletters, health fairs, word-of-mouth, and a prior research cohort. Ms and CHAMPS shared similar methodology and data collection tools so that the outcomes of interest could be compared by gender.…”
Section: Study Participantsmentioning
confidence: 99%